Verbal Aptitude Effect on The Inferential Skill in Reading of The Senior High School Age - Deborah Tirtania Chrisna Pake Seko (English Department - University of Sultan Ageng Tirtayasa, 2024)
As verbal aptitude is viewed as linguistic academic potency, this study aimed to investigate the correlation between students’ verbal aptitude and inferential skill in reading as well as to analyze the possibility for low verbal aptitude students to achieve high score in inferential skill test and identify the factors that influence students’ inferential skill in foreign language learning at senior high school age. A mixed study with sequential explanatory design in which Pearson Product Moment Correlation and interview were conducted in this study. The data were gathered from documentation, test, and interview of the selected sample using purposive and random sampling technique. The result revealed that the rXY is .651 and rtable at a significant level of 5% is .234, which means that rXY ≥ rtable with significant correlation 7.21 higher than r-table (1.99495). As a result, there is a strong significant correlation between students’ verbal aptitude and inferential skill in reading. Furthermore, the study also showed that students with low verbal aptitude (11%) can achieve high score in inferential skill but not as high as high verbal aptitude students’ scores. The factors that influence students’ inferential skills are age, motivation and interest, background knowledge, topics’ interest, working memory, language skills, personality, learning styles, and extended English course.